Análisis temporal de la evapotranspiración a partir de imágenes del sensor modis, en la cuenca del río sucio (chocó y antioquia) (2021)
This degree work aims to determine the temporal variability of evapotranspiration from images obtained from MODIS sensor, in the Sucio river basin (Chocó and Antioquia); For this, the historical evapotranspiration (ET) series collected from Terra and Aqua satellites were used, in a time window from 2001 to 2019 with a temporal resolution of 8 days for the variables "Total ET" and "Total Potential ET". A temporal time series was changed to a discrete time series, then a temporal characterization of evapotranspiration was carried out in a diurnal and monthly cycle, with the results obtained a statistical analysis was carried out where the main variable was the average. Among the main results is that for the Sucio river basin, the average monthly evaporation (ET) between the years 2001 and 2019 is 77 mm while the potential evapotranspiration (ETp) is 97 mm. In conclusion, it can be said that remote sensors allow a calculation of evapotranspiration to be carried out at the regional level in this way they serve as support to determine the amounts of water necessary in the irrigation of crops and contribute to the development of models that allow controlling natural phenomena such as floods.